2014
DOI: 10.1080/19393210.2013.876675
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and heavy metals in animal feed in Iran

Abstract: The occurrence of aflatoxin (aflatoxin B1, aflatoxin B2, aflatoxin G1 (AFG1) and aflatoxin G2 (AFG2)) and heavy metal (Pb, Cd, As and Hg) contamination was determined in 40 industrially produced animal feed samples which were collected from the southwest of Iran. The results indicated that 75% of samples were contaminated by four aflatoxins and the level of AFB1 and sum of aflatoxins were higher than the permissible maximum levels in Iran (5 and 20 µg kg(-1), respectively) in all feed samples. A positive corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
1
5
1
1
Order By: Relevance
“…As shown in Table 6, a positive and significant correlation was found between AFB 1 , AFB 2 , AFG 1 and AFG 2 levels in all feed samples (p < .01). Our findings are in agreement with previous studies (Borutova, Aragon, Nährer, & Berthiller, 2012;Eskandari & Pakfetrat, 2014). A positive and significant correlation among four types of investigated AFs in this study is due to the fact that A. parasiticus is able to produce AFGs and AFBs.…”
Section: Correlations Between Afb 1 Afb 2 Afg 1 and Afg 2 In Feedsupporting
confidence: 94%
“…As shown in Table 6, a positive and significant correlation was found between AFB 1 , AFB 2 , AFG 1 and AFG 2 levels in all feed samples (p < .01). Our findings are in agreement with previous studies (Borutova, Aragon, Nährer, & Berthiller, 2012;Eskandari & Pakfetrat, 2014). A positive and significant correlation among four types of investigated AFs in this study is due to the fact that A. parasiticus is able to produce AFGs and AFBs.…”
Section: Correlations Between Afb 1 Afb 2 Afg 1 and Afg 2 In Feedsupporting
confidence: 94%
“…Collectively, these observations indicate that AFM 1 contamination levels in milk vary among countries. These variations could be associated with different methods for toxin detection and differences in the forage and feed quality, cow diet, geographical location, climate and seasonal variations, genetic variation in dairy cows, farming systems, and feed storage [31,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In positive samples AFB 1 levels were below the maximum levels of the EU limit in feed for dairy cattle of 5 µg kg -1 (European Commission 2002). Eskandari and Pakfetrat (2014) reported the incidence of AFs in animal feeds in the southwest of Iran. Their results showed that 75% of the samples were contaminated with AFs and the level of AFB 1 in positive samples was above the accepted maximum level in Iran.…”
Section: Sample Analysismentioning
confidence: 98%